Competition for the International Pool of Talent: Education Policy and Student Mobility - Tim Krieger; Alexander M. Haupt; Thomas Lange (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The paper presents a model of two countries competing for the international pool of talented students from the rest of the world. To relax tuition-fee competition, countries differentiate their education systems in equilibrium, albeit inefficiently. One country offers high educational quality at high tuition fees and attracts the brightest students; the other country provides lower quality and charges lower fees. Recent developments, such as an increasing number of international students or growing graduate incomes in developing countries, widen the gap between education systems. Furthermore, educational competition among developed countries provides scope for a qualitative brain gain in less developed countries.
Keywords: H87; F22; I28; 330; Higher education; student mobility; vertical quality differentiation; return migration; brain gain